2000
DOI: 10.1136/jcp.53.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in house polymerase chain reaction with conventional techniques for the detection ofMycobacterium tuberculosisDNA in granulomatous lymphadenopathy

Abstract: Aims-To evaluate the usefulness of the devR based polymerase chain reaction (PCR) in the detection of Mycobacterium tuberculosis in lymph node aspirates and tissues of lymphadenitis and to compare PCR with conventional diagnostic techniques. Subjects and methods-Coded specimens of fine needle aspirates and biopsies from 22 patients with tuberculous lymphadenitis, 14 patients with non-tubercular lymphadenitis, and nine patients with granulomatous lymphadenitis were processed and subjected to analysis by PCR, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 24 publications
10
131
1
2
Order By: Relevance
“…Pode-se, portanto, concluir que a CAAF é uma ferramenta diagnóstica confiável para auxiliar a evitar procedimentos [25][26][27] .…”
Section: Discussionunclassified
“…Pode-se, portanto, concluir que a CAAF é uma ferramenta diagnóstica confiável para auxiliar a evitar procedimentos [25][26][27] .…”
Section: Discussionunclassified
“…The overall sensitivity of PCR was 70.83% in this study. Various studies have reported sensitivity ranging from 61% to 83% [15,18,20,21]. The low sensitivity can be explained due to the dilution of tubercle bacilli in non-spinal samples, such as synovial fluid and synovial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Novel targets have been exploited for diagnostic purposes by using PCR, namely, the devR response regulator gene (42,43), rRNA (5), selected chromosomal fragments (3,18,25,29), genes coding for the 65-kDa heat shock protein (36), the 38-kDa protein antigen (44), the dnaJ gene (47), and insertion sequences such as IS6110, IS990, and IS1081 (1,15,16,23); these are all examples of diverse targets that have been considered for PCR-based diagnostic approaches. Easy-to-use PCR kits targeting the rRNA gene for detection of M. tuberculosis are commercially available (Amplicor; Roche Molecular Systems, Branchburg, N.J.; GenProbe, Inc., San Diego, Calif.) (3,51,54), but it involves an additional step of DNA hybridization (3,14).…”
mentioning
confidence: 99%